Collaborative Mutual Identity Establishment (CMIE) for the future internet. Issue 4 (2nd November 2015) - Ambritta P, Nancy; Railkar, Poonam N.; Mahalle, Parikshit N.
Abstract : Purpose: – This paper aims at providing a comparative analysis of the existing protocols that address the security issues in the Future Internet (FI) and also to introduce a Collaborative Mutual Identity Establishment (CMIE) scheme which adopts the elliptical curve cryptography (ECC), to address the issues, such as content integrity, mutual authentication, forward secrecy, auditability and resistance to attacks such as denial-of-service (DoS) and replay attack. Design/methodology/approach: – This paper provides a comparative analysis of the existing protocols that address the security issues in the FI and also provides a CMIE scheme, by adopting the ECC and digital signature verification mechanism, to address the issues, such as content integrity, mutual authentication, forward secrecy, auditability and resistance to attacks such as DoS and replay attack. The proposed scheme enables the establishment of secured interactions between devices and entities of the FI. Further, the algorithm is evaluated against Automated Validation of Internet Security Protocols and Application (AVISPA) tool to verify the security solutions that the CMIE scheme has claimed to address to have been effectively achieved in reality. Findings: – The algorithm is evaluated against AVISPA tool to verify the security solutions that the CMIE scheme has claimed to address and proved to have been effectively achieved in reality. The proposed scheme enables the establishment of secured interactions between devices and entities of the FI. Research limitations/implications: – Considering the Internet of Things (IoT) scenario, another important aspect that is the device-to-location (D2L) aspect has not been considered in this protocol. Major focus of the protocol is centered around the device-to-device (D2D) and device-to-server (D2S) scenarios. Also, IoT basically works upon a confluence of hundreds for protocols that support the achievement of various factors in the IoT, for example Data Distribution Service, Message Queue Telemetry Transport, Extensible Messaging and Presence Protocol, Constrained Application Protocol (CoAP) and so on. Interoperability of the proposed CMIE algorithm with the existing protocols has to be considered to establish a complete model that fits the FI. Further, each request for mutual authentication requires a querying of the database and a computation at each of the participating entities side for verification which could take considerable amount of time. However, for applications that require firm authentication for maintaining and ensuring secure interactions between entities prior to access control and initiation of actual transfer of sensitive information, the negligible difference in computation time can be ignored for the greater benefit that comes with stronger security. Other factors such as quality of service (QoS) (i.e. flexibility of data delivery, resource usage and timing), key management and distribution also need to be considered. However, the user still has the responsibility to choose the required protocol that suits one's application and serves the purpose. Originality/value: – The originality of the work lies in adopting the ECC and digital signature verification mechanism to develop a new scheme that ensures mutual authentication between participating entities in the FI based upon certain user information such as identities. ECC provides efficiency in terms of key size generated and security against main-in-middle attack. The proposed scheme provides secured interactions between devices/entities in the FI.